Giant pattern VEPs in children. (September 2021) - Thompson, Dorothy A.; Marmoy, Oliver R.; Prise, Katrina L.; Reynolds, Victoria M.; Handley, Sian E.; Versace, Dominique M.; Kafiabadi, Sina; Mankad, Kshitij; Panteli, Vasiliki; Schwiebert, Kemmy; James, Greg; Bowman, Richard
Abstract: Our aim is to elaborate the clinical significance of giant amplitude pattern reversal visual evoked potentials (VEPs) in children. 'Giant' amplitude VEPs exceed the upper 97.5 th centile, 90% CI for age. We scrutinised 2750 pattern VEPs recorded to international standards between Jan 2015 and 2017 from children aged 16 years and under, attending a specialist children's hospital. Twenty seven children, median age 6yrs, (range 1–16 yrs), were identified with giant VEPs (P100 amplitude range 65–163 μV). Most, 22/27 (81%), had conditions associated with a risk of raised ICP. Sixteen of these twenty two children had craniosynostosis; six multi-sutural and eight single suture disease. Others had Idiopathic Intracranial Hypertension, arachnoid cyst, NF1 with shunted hydrocephalus, chronic infantile neurological cutaneous and articular (CINCA) syndrome, nephrotic cystinosis and obstructive sleep apnoea. Five children presented with a range of conditions, some associated with seizures some symptomatic, but as yet undiagnosed. Frequent structural associations were optical coherence tomography measures of optic disc maximum anterior axial horizontal retinal thickness projection >160 μm and neuro-radiological findings of CSF effacement and copper beaten appearance. Ultrasonography measures of optic nerve sheath diameters varied, but in one child took 2 years to resolve after treatment for raised ICP. Optic disc gradings by fundoscopy were mostly normal, as were visual acuities. Raised ICP was confirmed by gold standard ICP bolt measurements in five of seven children tested. These data suggest that rICP should be considered if a child has sustained giant amplitude VEPs at normal latency. Highlights: Giant VEPs larger than 65 μV can be generated by children at risk of raised ICP. Giant VEPs associate with OCT horizontal optic disc protrusion exceeding 160 μm. Increases in VEP amplitude can precede OCT optic disc changes. rICP and thinned CSF layer may provoke cortical hyper-excitability and giant VEPs.